Karakteristik Tapai Ketan Hitam Hasil Teknik Pemasakan yang Berbeda - Marniza Marniza; Syafnil Syafnil; Sari Safitri (Jurnal Teknologi Agro-Industri, 2020)
Tapai ketan hitam is Indonesian traditional food that fermented glutinous rice. In Bengkulu City, the tapai ketan hitam is sole at Lingkar Barat, Bengkulu City. The production of the tapai ketan hitam different on cooking methods, which boiling or steaming method. The aim of research was to obtain the characteristic of fermented glutinous rice that cooked with boilling or steaming. Characteristic of the tapai ketan hitam was relatively not different for boiling and steaming methods. The characteristics of black tapai were pH 4.8, ethanol content 1.5%, reduced sugar 10.97 and 11.54 %, red purple colour, soft texture and tapai specific aroma.